Functional and Short-term Outcomes in Elective Laparoscopic Colectomy for Symptomatic Diverticular Disease With Either Low Ligation or Inferior Mesenteric Artery Preservation: A Randomized Trial. Issue 1 (February 2021) - Mari, Giulio; Montroni, Isacco; Origi, Matteo; Crippa, Jacopo; Achilli, Pietro; Costanzi, Andrea; Ferrari, Giovanni; Ugolini, Giampaolo; Maggioni, Dario
Abstract : Background: The current treatment of symptomatic diverticular disease is left colectomy/sigmoidectomy with low ligation of the inferior mesenteric artery versus the inferior mesenteric artery preservation. Up to now, there is no strong evidence in favor of one of the 2 strategies. The aim of this study is to compare the bowel-specific quality of life and functional outcomes between these 2. Methods: Between June 2015 and February 2019, patients were randomly assigned to inferior mesenteric artery low ligation or inferior mesenteric artery preservation during elective laparoscopic sigmoidectomy for diverticular disease. Gastrointestinal, genitourinary functions and surgical outcomes were compared postoperatively between groups. Results: One-hundred sixty-eight patients were randomized providing 2 homogenous groups. Gastrointestinal and genitourinary functions were not significantly different between groups after 1 and 6 months postoperative. In both groups, the function was restored to the preoperative level 6 months after surgery. There was no statistically significant difference in terms of conversion rate, blood loss, length of surgery, between groups. There was no difference in the overall complication rate and the anastomotic leak rate among groups. Conclusions: Inferior mesenteric artery low ligation or inferior mesenteric artery preservation during elective laparoscopic sigmoidectomy for a diverticular disease can be considered equivalent in affecting the postoperative bowel-related quality of life, genitourinary function, and surgical outcomes.